0y=ox

Simple and best practice solution for 0y=ox equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0y=ox equation:


Simplifying
0y = ox

Anything times zero is zero.
0y = ox

Solving
0 = ox

Solving for variable 'o'.

Move all terms containing o to the left, all other terms to the right.

Add '-1ox' to each side of the equation.
0 + -1ox = ox + -1ox
Remove the zero:
-1ox = ox + -1ox

Combine like terms: ox + -1ox = 0
-1ox = 0

Divide each side by '-1'.
ox = 0

Simplifying
ox = 0

The solution to this equation could not be determined.

See similar equations:

| 2(x+2)/8=5 | | 111-3x=15x+23 | | 15x-275=6x-5 | | s=2hw+2wh+2hl | | 6x-119=2x-7 | | 24f-16fg= | | y/2+5=16 | | 6w+w+8w= | | 14x-190=4x-10 | | 6w-w+6w= | | 2x+65=7x-10 | | 9-7X=9X+21 | | -126-8x=16x+18 | | 5(3x+5)-4(2x-3)=5x+3(2x+12)+1 | | 11x+8=8x-29 | | 59-4x=32x+15 | | -28X-6X=12-10X | | 14-9x=199-44x | | 3+7x=27+1x | | 11X+22=4X+113 | | 2.16x^2-5.40x-3.24=0 | | 60-x=19 | | x-6/10+x-4/15=x+2/6 | | 12*(x-2)+6*(5-x)=4x-6 | | x^4+12x^3+36x^2-64=0 | | 5w^8-45w^7-50w^6=0 | | 3x-4(1-3x)=2x-(x-1) | | 3(x+2)/5=6 | | 4-2(3-2x)=5 | | X+x+x=16 | | 3-5(2x+1)=2x | | 3y^2-9y-84=0 |

Equations solver categories